The Sour Grape - John, Jory; Oswald, Pete Ilustrador (New York : HarperCollins, 2019)
The Sour Grape holds grudges for every reason under the sun. Lime never returned a scarf they borrowed? Grudge! Orange never called back? Grudge! But when a friend holds a grudge against the Sour Grape without listening to an explanation, the Sour Grape realizes how unfair grudges can be. Could a bunch of forgiveness and compassion be enough to turn a sour grape sweet?
4 - 8 anos